Metabolomic and Proteomic Analysis of Maize Embryonic Callus induced from immature embryo - Fei Ge (Nature Portfolio, 2017)
Abstract The low ratio of embryonic callus (EC) induction has inhibited the rapid development of maize genetic engineering. Still, little is known to explain the genotype-dependence of EC induction. Here, we performed a large-scale, quantitative analysis of the maize EC metabolome and proteome at three typical induction stages in two inbred lines with a range of EC induction capabilities. Comparison of the metabolomes and proteomes suggests that the differential molecular responses begin at an early stage of development and continue throughout the process of EC formation. The two inbred lines show different responses under various conditions, such as metal ion binding, cell enlargement, stem cell formation, meristematic activity maintenance, somatic embryogenesis, cell wall synthesis, and hormone signal transduction. Furthermore, the differences in hormone (auxin, cytokinin, gibberellin, salicylic acid, jasmonic acid, brassinosteroid and ethylene) synthesis and transduction ability could partially explain the higher EC induction ratio in the inbred line 18-599R. During EC formation, repression of the “histone deacetylase 2 and ERF transcription factors” complex in 18-599R activated the expression of downstream genes, which further promoted EC induction. Together, our data provide new insights into the molecular regulatory mechanism responsible for efficient EC induction in maize.